The Ketogenic Diet for Refractory Mental Illness: A Retrospective Analysis of 31 Inpatients - Danan, Albert; Westman, Eric C.; Saslow, Laura R.; Ede, Georgia (Frontiers in Psychiatry, 2022)
Abstract Background and Hypothesis The robust evidence base supporting the therapeutic benefit of ketogenic diets in epilepsy and other neurological conditions suggests this same metabolic approach may also benefit psychiatric conditions. Study Design In this retrospective analysis of clinical care, 31 adults with severe, persistent mental illness (major depressive disorder, bipolar disorder, and schizoaffective disorder) whose symptoms were poorly controlled despite intensive psychiatric management were admitted to a psychiatric hospital and placed on a ketogenic diet restricted to a maximum of 20 grams of carbohydrate per day as an adjunct to conventional inpatient care. The duration of the intervention ranged from 6 to 248 days. Study Results Three patients were unable to adhere to the diet for greater than 14 days and were excluded from the final analysis. Among included participants, means and standard deviations (SDs) improved for the Hamilton Depression Rating Scale scores from 25.4 (6.3) to 7.7 (4.2), P <.001 and the Montgomery−Åsberg Depression Rating Scale from 29.6 (7.8) to 10.1 (6.5), P <.001. Among the 10 patients with schizoaffective illness, mean (SD) of the Positive and Negative Syndrome Scale (PANSS) scores improved from 91.4 [15.3] to 49.3 [6.9], P <.001. Significant improvements were also observed in metabolic health measures including weight, blood pressure, blood glucose, and triglycerides. Conclusions The administration of a ketogenic diet in this semi-controlled setting to patients with treatment-refractory mental illness was feasible, well-tolerated, and associated with significant and substantial improvements in depression and psychosis symptoms and multiple markers of metabolic health.